Using Python to analyze multiple countermovement vertical jumps over time - Smith, J. C. (Strength and Conditioning Journal, 2024)
Countermovement vertical jumps (CMVJs) can be used for athletic monitoring. When performed on a force plate, biomechanical variables can be obtained to identify factors relating to performance. Commercially available software can be purchased to analyze metrics relating to CMVJs. Users are typically limited to metrics provided by these "black box" setups. However, some commercial products provide export functions for users to manipulate raw data. These programs often require additional components to complete the analysis, which could be cost prohibitive. The purpose of this article is to compare using Excel, MATLAB, R, and Python to analyze multiple CMVJ trials, so practitioners have more control over how metrics are determined rather than relying on the "black box" setup with or without the expense of third-party proprietary software. This guide will introduce Python by presenting a template for analyzing force plate jump data. Strategies for reading files, filtering data, calculating biomechanical variables, graphically representing data, and writing results to a master data file will be discussed. Although the provided script can be used to analyze CMVJ data by itself, it can be modified to include other metrics the practitioner wishes to include in their setting (see Supplemental Digital Content 1, https://links.lww.com/SCJ/A383).